2018
DOI: 10.4103/jpn.jpn_86_18
|View full text |Cite
|
Sign up to set email alerts
|

Posterior fossa acute extradural hematoma in children: Review and management guidelines

Abstract: Posterior fossa acute extradural hematoma is a rare but potentially fatal disease in children. This article reviews the literature on this topic and offers an evidence based guideline for management of the same.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 26 publications
0
23
0
1
Order By: Relevance
“…For those reasons, it is not possible to report a more precise incidence of this pathology. PFEH shows a reduced incidence in population [1-3]. Kaushik and Sandip, in an interesting review of the literature on this topic, in the period between 1957 and 2000, found only 157 articles [3].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 4 more Smart Citations
“…For those reasons, it is not possible to report a more precise incidence of this pathology. PFEH shows a reduced incidence in population [1-3]. Kaushik and Sandip, in an interesting review of the literature on this topic, in the period between 1957 and 2000, found only 157 articles [3].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…PFEH shows a reduced incidence in population [1-3]. Kaushik and Sandip, in an interesting review of the literature on this topic, in the period between 1957 and 2000, found only 157 articles [3]. Chagou et al [1] report that the incidence of PFEH, in a series of 600 pediatric patients was 1.5% while Sencer et al [5] showed a series of 40 cases of pediatric patients with PFEH with an incidence of 8.5%.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 3 more Smart Citations